Psychic trauma and post traumatic stress disorder. Judith Herman: Therapeutic approach - Morales Miranda, Carmen (Universidad Femenina del Sagrado Corazón, 2018)
People who suffer from post traumatic stress are usually reluctant to ask for any kind of help, except forpsychotherapy. Recovery will be based on the survivor empowerment and the healing of his new connections,since this recovery can only happen in the context of relationships and not in isolation. His renewed connectionswith the medium will allow him to recreate the damaged or deformed psychological faculties caused by traumaticexperience and to recover his basic capacities such as trust, autonomy, initiative, competence, identity andintimacy.